2019
DOI: 10.21037/acs.2018.05.18
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the financial cost of robotic lobectomy: calculating the value of innovation?

Abstract: Background: The advantages of a minimally-invasive surgical approach compared to conventional open thoracotomy for lung resection have been previously described. While robot-assisted thoracoscopic surgery (RATS) has shown comparable clinical outcomes for lobectomy as compared with video-assisted thoracic surgery (VATS), the cost and inherent value associated with the robotic technology remains a main concern. Methods: We conducted a systematic review of the literature on the cost of RATS lobectomy using studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 22 publications
0
41
1
Order By: Relevance
“…In a recent systematic review of published studies on cost of robotic lobectomy, we have shown that there is great variability among institutions, ranging between $15,440 and $22,582 for median hospital cost. 21 We showed that the greatest hospital costs of robotic lobectomy were calculated from registry data, reflecting the early robotic experience. 7,13 By contrast, the lowest costs associated with robotic lobectomy were reported from a high-volume center, which also reported the lowest complication rates and shortest hospital stay.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a recent systematic review of published studies on cost of robotic lobectomy, we have shown that there is great variability among institutions, ranging between $15,440 and $22,582 for median hospital cost. 21 We showed that the greatest hospital costs of robotic lobectomy were calculated from registry data, reflecting the early robotic experience. 7,13 By contrast, the lowest costs associated with robotic lobectomy were reported from a high-volume center, which also reported the lowest complication rates and shortest hospital stay.…”
Section: Discussionmentioning
confidence: 91%
“…Total indirect costs are the sum of all additional costs for the hospital that is comprised of overhead cost and amortization of capital equipment, including of the purchase and maintenance of minimally invasive platforms, as previously outlined. 21 Operating room cost as a fraction of total direct hospital cost was available for years 2012 to 2015. After 2015, cost data were available on a more granular level by cost centers, which were compared separately.…”
Section: Measures Of Cost and Clinical Effectivenessmentioning
confidence: 99%
“…88 A recent meta-analysis by Singer et al affirmed these findings, with the cost of robotic lobectomy ranging from $2,901 to $4,708 higher than VATS lobectomy. 89 Robotic lobectomy was also more expensive than open lobectomy, but these cost differences were not statistically significant.…”
Section: Other Approaches For Minimally Invasive Lobectomy Robotic Lomentioning
confidence: 95%
“…This conflicts with Kneuertz and colleagues' 1 own previous literature review, which showed a $2901-$4708 premium for robotic relative to thoracoscopic lobectomy. 2 Caution is imperative in interpreting these results and in using the data for the overly enthusiastically promotion of robotic surgery. The use of inverse probability of treatment weighting to eliminate as much bias in patient selection as possible is a positive step, but not a perfect one.…”
mentioning
confidence: 99%